RhCu 3D Nanoframe as a Highly Active Electrocatalyst for Oxygen Evolution Reaction under Alkaline Condition. Issue 4 (25th September 2015) - Park, Jongsik; Kim, Jongchan; Yang, Yoojin; Yoon, Donghwan; Baik, Hionsuck; Haam, Seungjoo; Yang, Haesik; Lee, Kwangyeol
Abstract : One pot synthesis of RhCu alloy truncated octahedral nanoframes, Cu@Rh core–shell nanoparticles, and a bundle of five RhCu nanowires is demonstrated. The RhCu alloy 3D nanoframe, in particular, exhibits excellent catalytic activity toward the oxygen evolution reaction under alkaline conditions.